Legalidade e legitimidade no licenciamento ambiental de empreendimentos de impacto de iniciativa do poder público municipal em Belo Horizonte - Maria Auxiliadora de Moraes Moreira (2007)
The emergency of environmental license in Belo Horizonte has happened like in many places, more from a social demand caused by complains and denunciations, than for legal exigencies.Although the existence of federal, departmental and municipal laws, like the Federal law # 6.938/81, that has instituted the Environmental National Policy, and created environmental impact evaluation, the environmental license has only been institutionally practiced by the city administration after the municipal law # 7.277s sanction in January 17, 1997, that instituted the environmental license in the city. We think that the emergency and the institutional process of urban and environmental license are processes of difficult maturing and equating. One of the difficulties found in this question is the dichotomy existent between the urban and environmental aspects, therefore these concepts need to dialog each other, considering that they are not isolated phenomenon, but integrated. Another challenge is to effect the city social function, introduced by the 1988s Federal Constitution, and realize that the city is a collective production, instead of a State one, and apply the societys participation tools in its planning and administration, brought by the City Statute in 2001. This study starts with contemporary urban theories, adopting new paradigms able to discuss the environmental urban license process of public impact projects in Belo Horizonte city, under the vision of environmental urban laws and social participation. We propose a reflection about Boaventura de Sousa Santoss thought about science to explain the dichotomy between theory and practice, legality and legitimacy. We took the Belo Horizontes case of its New Bus Station environmental urban license process to compare the license by the environmental method, the Environmental Impact Study with a new instrument became from political roots, the Neighborhood ImpactStudy, brought by 2001s City Statute. This essay aimed to verify the construction of new social proposes in direction of social participation increase, through legal instruments, supposed as public and private interests mediators in urban and environmental license processes of municipal impact projects.